ผลของการเติมอะลูมิเนียมและไทเทเนียมในโลหะผสมพิเศษเกรด Hastelloy X ที่ผลิตด้วยการหลอมอาร์กต่อโครงสร้างจุลภาคและความต้านทานการเกิดออกซิเดชัน - ปาจรีย์ ศรีเกี่ยวฝั้น (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This work had an attempt to modify solid solution strengthening nickel base alloy, grade Hastelloy X by additions of Aluminium, Titanium and both Aluminium plus Titanium (50:50) in order to form more precipitated intermettalic phase for higher mechanical properties and better oxidation resistance. The alloys were melted and casted in vacuum arc melting furnace. Aluminium, Titanium and both Aluminium plus Titanium were added in Hastelloy X for 2, 4, 6%wt. The as-cast specimens were heat treated with solutioning treatment at temperature of 1175 degree Celsius for 4 hours and then aged at different temperatures of 760, 800 and 845 degree Celsius for 24 hours. After that all specimens were analyzed by X-Ray Fluorescence. The microstructures of all specimens were observed and investigated by optical microscope, scanning electron microscope, and X-Ray diffractrometer. Furthermore, oxidation behaviors of the selected specimens were tested at temperatures of 900 degree Celsius and 1,000 degree Celsius for 100 hours. The oxide films were characterized by X-Ray diffratrometer. The obtained results showed that the element additions significantly changed the observed microstructure. More element additions resulted in more intermettalic phase precipitations such as sigma and etha phases. The expected gamma prime phase was only found in the specimens with Aluminium additions. The specimens with Aluminium addition performed the best oxidation resistance. The alumina film was found in specimens with only Aluminium addition. Titanium oxide film was found in specimens with Titanium and both Aluminium plus Titanium additions.